Is Elevation of Alkaline Phosphatase a Predictive Factor of Response to Alectinib in NSCLC? - Walid Shalata; Alexander Yakobson; Rachel Steckbeck; Ashraf Abu Jama; Omar Abu Saleh; Abed Agbarya (Current Oncology, 2021)
In the following report, we describe a case of alkaline phosphatase (ALP) elevation occurring during treatment with alectinib (Alecensa™), which was administered for anaplastic lymphoma kinase (ALK) mutated metastatic non-small cell lung cancer (mNSCLC). A 51 year-old female with widespread metastatic disease exhibited a rapid and significant response within a very short period to alectinib therapy, accompanied by a rapid increase of ALP to more than six times the upper limit of normal (grade 3) ALP, decreasing to within normal limits within 3 weeks after initiation of therapy without any dose modification.